2017
DOI: 10.1016/j.jad.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The metacognitions about self-critical rumination questionnaire

Abstract: The MSCRQ appears to be a reliable and valid measure of metacognitions about self-critical rumination whilst the MCQ-30 is a better predictor of general emotional distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
0
13
1
3
Order By: Relevance
“…their symptoms. Neither self-critical rumination nor the associated negative metacognitions were significant predictors of negative affect when controlling for generic negative metacognitions (Kolubinski et al, 2017). This suggests that the process of self-critical rumination may mediate the relationship between depression and self-esteem, but this relationship may not be reciprocal.…”
Section: Addressing the Aims Of The Studymentioning
confidence: 76%
See 1 more Smart Citation
“…their symptoms. Neither self-critical rumination nor the associated negative metacognitions were significant predictors of negative affect when controlling for generic negative metacognitions (Kolubinski et al, 2017). This suggests that the process of self-critical rumination may mediate the relationship between depression and self-esteem, but this relationship may not be reciprocal.…”
Section: Addressing the Aims Of The Studymentioning
confidence: 76%
“…predict levels of emotional distress when controlling for generic metacognitions (Kolubinski et al, 2017). In order to ascertain whether this is true with respect to self-esteem, we hypothesized that self-critical rumination, and its associated metacognitions, should predict levels of self-esteem whilst controlling for generic metacognitions.…”
Section: Study Objectives and Hypothesesmentioning
confidence: 99%
“…In accordance with the S-REF model, Kolubinski et al (2016Kolubinski et al ( , 2017 identified that positive and negative metacognitions are involved in self-critical rumination, as have been identified in other emotional, physical and behavioral domains Fernie et al 2015Fernie et al , 2017Nikčević et al 2017;Papageorgiou and Wells 2001a;Spada and Wells 2006). In this model, positive metacognitions refer to beliefs linked to the activation of the ruminative process (e.g.…”
Section: Self-critical Rumination and Metacognitionsmentioning
confidence: 55%
“…Recently, researchers have started to explore the role that the process of rumination plays in maintaining levels of self-critical thinking, distress and selfesteem (Kolubinski et al 2017;Moreira and Canavarro 2018;Smart et al 2016). Rumination is the process of perseveratively thinking about one's emotions or problems without actively problem-solving.…”
Section: Self-criticism and Self-critical Ruminationmentioning
confidence: 99%
“…(Kolubinski, Lawrence, Spada, 2017) Self-Critical (kritik diri) Mengacu pada serangkaian penilaian diri yang terus-menerus dan negatif, yang seringkali tidak disengaja, yang dibuat seseorang tentang diri mereka sendiri.…”
Section: Self-critical Rumination Questionnaire (Scrq)unclassified